2015
DOI: 10.1186/s40885-015-0019-4
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation of flow-mediated dilatation in healthy humans

Abstract: IntroductionThe measurement of flow-mediated dilatation (FMD) via ultrasound has been established as a reliable non-invasive measurement of endothelial function. However, the guidelines mention nothing regarding diurnal variation of FMD. Thus, we investigated the FMD in healthy people and diurnal variation of FMD.MethodsTwenty-five apparently healthy persons participated in this study. All participants had no history of cardiovascular diseases, hypertension, or diabetes and used any medication. For each volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…We did not have a control group in this study, although all comparisons are made within subjects. Time of day may influence FMD (Jones et al 2009 ; Al Mheid et al 2014 ), although findings are equivocal (Kim et al 2015 ). Consequently, all efforts were made to retest all subjects at the same time of the day for all repeat measurements.…”
Section: Discussionmentioning
confidence: 99%
“…We did not have a control group in this study, although all comparisons are made within subjects. Time of day may influence FMD (Jones et al 2009 ; Al Mheid et al 2014 ), although findings are equivocal (Kim et al 2015 ). Consequently, all efforts were made to retest all subjects at the same time of the day for all repeat measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Although contraceptive use was consistent throughout the testing period, it could impact vascular function (Friedman et al, 2011). Despite the diurnal variation of vascular function remaining contentious (Bau et al, 2008; Jarvisalo et al, 2006; Kim et al, 2015), subjects were encouraged and primarily attended similar testing times across visits, although this was not always possible, and some visit start times may have varied ~4 h throughout the day. Although vascular function alterations within the menstrual cycle may be minimal (Williams et al, 2020), female participants reported to the lab at 1‐month intervals which minimized menstrual cycle fluctuations in vascular function within participants, while the cycle phase between participants was not controlled for.…”
Section: Discussionmentioning
confidence: 99%
“…However, days 1-5 and the placebo pill phase correspond to the lowest plasma estradiol levels in women who have natural menstrual cycles and those taking oral contraceptives, respectively (7,42,54). The time of day when the vascular assessments were conducted varied between participants (i.e., beginning from 8:30 AM to 4 PM), which may (23,32,36,49) or may not (3,24) influence endothelial function. Importantly, men and women were tested at a similar time of day (men: 12:09 PM Ϯ 2.44 h; women: 11:49 AM Ϯ 3.75 h; P ϭ 0.76), and a similar proportion of each sex was tested in the morning (men: n ϭ 5; women: n ϭ 6) and afternoon (men: n ϭ 5; women: n ϭ 4).…”
mentioning
confidence: 99%